2007
DOI: 10.1016/j.adt.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact collision strengths in Si IX, Si X, and Si XI

Abstract: Electron impact collision strengths among 560 levels of Si IX, 320 levels of Si X, and 350 levels of Si XI have been calculated using the Flexible Atomic Code of Gu [M.F. Gu, Astrophys. J. 582 (2003) 1241]. Collision strengths X at 10 scattered electron energies, namely 10, 50, 100, 200, 400, 600, 800, 1000, 1500, and 2000 eV, are reported. Assuming a Maxwellian energy distribution, effective collision strengths Ç are obtained on a finer electron temperature grid of 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, and 6.0 MK, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…2d) which connects the two sets. Excellent agreement is found between our background collision strengths and the DW results of Liang et al (2007).…”
Section: Collision Strengthssupporting
confidence: 80%
See 4 more Smart Citations
“…2d) which connects the two sets. Excellent agreement is found between our background collision strengths and the DW results of Liang et al (2007).…”
Section: Collision Strengthssupporting
confidence: 80%
“…This is most likely due to resonances attached to n = 3 which were not described by Keenan et al Furthermore, at high temperatures, we observed incongruous behaviour in their effective collision strengths for many dipole transitions. For the n = 2 → 3 excitation rates, the present results are higher than previously available Sampson 1994 andLiang et al 2007) non-resonant DW data, and can be so by more than an order of magnitude for many transitions at low temperatures ( < ∼ 5 × 10 5 K). Here, the difference peaks in the range 1 × 10 4 < ∼ T e (K) < ∼ 1 × 10 5 , and so is of likely importance for photoionized plasmas.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations